Immunological aspects of antiviral therapy of chronic hepatitis B virus and hepatitis C virus infections. Issue 2 (February 2015) - Rehermann, Barbara; Bertoletti, Antonio
<x xml:space="preserve">Abstract</x> Hepatitis B virus (HBV) and hepatitis C virus (HCV) cause a large proportion of acute and chronic liver disease worldwide. Over the past decades many immunological studies defined host immune responses that mediate spontaneous clearance of acute HBV and HCV infection. However, host immune responses are also relevant in the context of treatment‐induced clearance of chronic HBV and HCV infection. First, the pretreatment level of interferon‐stimulated genes as well as genetic determinants of innate immune responses, such as single nucleotide polymorphisms near the IFNL3 gene, are strong predictors of the response to interferon‐alpha (IFN‐α)‐based therapy. Second, IFN‐α, which has been a mainstay of HBV and HCV therapy over decades, and ribavirin, which has also been included in interferon‐free direct antiviral therapy for HCV, modulate host immune responses. Third, both IFN‐α‐based and IFN‐α‐free treatment regimens of HBV and HCV infection alter the short‐term and long‐term adaptive immune response against these viruses. Finally, treatment studies have not just improved the clinical outcomes, but also provided opportunities to study virus‐host interaction. This review summarizes our current knowledge on how a patient's immune response affects the treatment outcome of HBV and HCV infection and how innate and adaptive immune responses themselves are altered by the different treatment regimens. ( Hepatology 2015;61:712‐721)